Combining multi-criteria and space syntax analysis to assess a pedestrian network: the case of Oporto - Jabbari, M. (2018)
This paper describes a GIS-based integrated approach to assess a pedestrian network by combining multi-criteria and space syntax. The analysis combines pedestrian attributes with street connectivity and both factors were evaluated by a group of experts. The approach was adopted in the city of Oporto. Results show that the city centre offers various conditions; however, overall they are poor for pedestrians. Moreover, the streets which scored best are not integrated into the network. The described approach can potentially be replicated in other cities in terms of improving the walkability and promoting sustainable urban mobility.